Development and Optimization of Facial Wash Gel with Okra Fruit (Abelmoschus esculentus) Extract: a Study on HPMC Concentration Variations - Ana Yulyana; Annisya Maulidia Putri; Eko Mugiyanto (Faculty of Pharmacy Universitas Pancasila, 2025)
The stability of facial wash gel formulations is influenced by the concentration of Hydroxypropyl Methylcellulose (HPMC), which plays a crucial role in determining viscosity, homogeneity, spreadability, and foam stability. This study aimed to evaluate and optimize the physical stability of facial wash gel containing okra extract 3% (Abelmoschus esculentus (L.) Moench) by varying HPMC concentrations (1, 1.5, and 2%). The formulations were assessed for homogeneity, syneresis, pH stability, viscosity, spreadability, and foam stability over a 28-day storage period at room temperature (25°C). Statistical analysis was performed using SPSS version 27, including Shapiro-Wilk normality test, Levene’s test for homogeneity, One-Way ANOVA, and Tukey’s post-hoc test to determine significant differences among formulations. The results showed that HPMC concentration significantly influenced gel stability. F1 (1% HPMC) exhibited syneresis, excessive spreadability, and lower viscosity, indicating poor structural integrity. F2 (1.5% HPMC) maintained moderate stability but showed significant changes in spreadability over time. F3 (2% HPMC) demonstrated the best stability with optimal viscosity, minimal syneresis, controlled spreadability, and consistent foam formation. pH values for all formulations remained within the acceptable range (4.5–7.8, SNI 16-4380-1996). Foam stability (60–70%) met regulatory standards (SNI 16-4085-1996), with higher HPMC concentrations contributing to increased foam retention. The study confirms that HPMC concentration is a key determinant of gel stability. F3 (2% HPMC) exhibited the most stable formulation, balancing viscosity, spreadability, and foam stability, making it the optimal formulation for facial wash gel development. These findings highlight the importance of gelling agent optimization in cosmetic formulations, ensuring both product stability and consumer acceptability.